ACADEMIC STRESS AND COPING STRATEGIES AMONG UNIVERSITY STUDENT - Djoldasbayeva Ayzada Rustemovna (International Journal of Literature and Language Studies, 2026)
Academic stress has become one of the most significant psychological challenges affecting university students worldwide. The increasing demands of higher education, including examinations, assignments, academic competition, and future career concerns, contribute to elevated stress levels among students. This study investigates the major sources of academic stress and explores the coping strategies employed by university students to manage stress effectively. A review of contemporary literature indicates that academic stress negatively influences students’ mental health, academic performance, motivation, and overall well-being. The findings suggest that effective coping mechanisms such as time management, social support, physical activity, and psychological resilience can significantly reduce the adverse effects of academic stress. The study highlights the importance of institutional support systems and stress management programs in promoting students’ academic success and psychological health.